Islamic Counseling Guidance Strategy in Preventing Gender-Based Domestic Violance / Strategi Bimbingan Konseling Islam dalam Mencegah Kekerasan dalam Rumah Tangga Berbasis Gender - Ulfa, Handini Marliana; Algifahmy, Ayu Faiza (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2025)
The increasing number of people in the National Commission on Violence Against Women report in 2024 as many as 4,178 affected by domestic violence (KDRT) especially in the context of gender, one effective method to prevent gender-based domestic violence is the Islamic counseling guidance approach. This study investigates the best Islamic counseling guidance method to prevent domestic violence. This research was conducted by conducting library research by exploring journals, books, and reference sources that are relevant to the research topic. Focus on Islamic literature related to marriage, the rights and obligations of husband and wife, and Islamic values ​​that are relevant to the prevention of Domestic Violence (KDRT). The results of the study indicate that there are several Islamic counseling guidance strategies that can be applied, including: instilling the values ​​of gender equality and anti-violence through an Islamic approach, family counseling with an Islamic approach to resolve conflicts, building healthy communication, empowering women's economy to increase independence and reduce dependence, and the formation of community and religious-based support groups through counseling services, health education, family health posts, routine study groups, social activities and humanitarian assistance. The results of this study provide knowledge for counseling practitioners and related parties on how to prevent domestic violence that is sensitive to gender and Islamic values ​​in the form of pre-marital counseling and education, Islamic counseling services, training for religious leaders, and spiritual guidance which are effective means of building awareness, changing behavior, and strengthening family resilience.